O sistema modular de ensino em escolas do campo do município paraense de Tomé-Açu: uma pesquisa participante - OLIVEIRA, Maria Michelle Lima da Silva de (2022)
This paper presents the results of a qualitative research developed in 2019, with the aim of knowing and discussing obstacles and possibilities for the promotion of school teaching appropriate to the educational needs of students in the last four years of elementary education in four schools of rural education in the municipality of Tomé-Açu, Pará, submitted to the Modular Organizational System, the System of Alternating Cycle and teaching by interdisciplinary projects. It is a research based on the dialectic method to discuss and reflect about the educational reality in rural areas. In this way, it was guided by the official national and municipal curriculum documents. As achieved results, the study highlighted the contextualization of the curriculum with the students' experiences, emphasizing the problems and the strategies developed to guarantee the offer of a more useful, feasible and contextualized school education.